Information security policies, procedures, and standards : a practitioner's reference - Landoll, Douglas J. (CRC Press, 2016)
Highlighting key terminology, policy development concepts and methods, and suggested document structures, this practical guide includes examples, checklists, sample policies and procedures, guidelines, and a synopsis of the applicable standards. --